Chemical mismanagement and skin burns among hospitalized and outpatient department patients. Issue 3 (3rd July 2021) - Majeed, Salman; Rahman, Mati Ur; Majeed, Hammad; Rahman, Sami Ur; Hayat, Asif; Smith, Sandra D.
Abstract : Purpose . This article attempts to elucidate the nature of chemicals causing major and minor skin burns, and their associated characterization across different industries, using Fujian provincial hospitals' admission and outpatient department records. Materials and methods . Data were collected from the provincial hospitals of Fujian through a questionnaire, sent via email, from June 1, 2017 to November 30, 2017. The collected responses were statistically analyzed using SPSS version 19 through the interquartile range, median, Mann–Whitney U test and Fisher's exact test with two-tailed significance. Results and conclusions . The results of 306 collected responses reveal that the majority of skin burn cases are due to a lack of technical education and professional training among workers handling chemicals. This study suggests that management's effective supervision and governmental regulations may help to prevent chemical skin burns at work, and can further be controlled by hiring professional workers alongside providing training to them in chemical handling as well as using protective equipment and developing appropriate management policies to improve victims' well-being and quality of life. Findings will help workers, doctors, hospitals, industries, government and other stakeholders to understand and control chemical hazards on site to minimize the risks of chemical skin burn incidents.